On the mechanism of Zn4O-acetate precursors ripening to ZnO: How dimerization is promoted by hydroxide incorporation - Segets, Doris; Milek, Theodor; Kirschbaum, Rolf; von Gernler, Marc; Lübbert, Christian; Drewello, Thomas; Peukert, Wolfgang; Zahn, Dirk (Journal of Chemical Physics, 2015)
We report on a combined experimental and molecular modelling study on Zn4O ion clusters stabilized by acetate molecules (OAc). In particular, ab initio calculations of acetate substitution by hydroxide ions are compared with mass spectrometry data. Though quantum calculations in the gas phase indicate strong energetic preference, no experimental evidence of stable Zn4O(OAc)6−x(OH)x clusters in ethanolic solutions could be observed. This apparent contradiction is rationalized by identifying the supportive role of hydroxide ions for the association of (OAc− → OH− substituted) Zn4O(OAc)6 and Zn4O(OAc)5+ clusters. Mass spectrometry and quantum calculations hint at the stability of (Zn4O)2(OAc)12−x(OH)x dimers with x = 1, 2. Therein, the hydroxide ions establish salt-bridges that allow for the formation of additional Zn3 motifs with the OH above the triangle center—a structural motif close to that of the ZnO-crystal. The association of Zn4O(OAc)6 clusters is thus suggested to involve OAc− → OH− substitution as an activation step, quickly followed by dimerization and the subsequent agglomeration of oligomer
Keywords: mechanism; particle; rod; nano; ripening